Beyond the public sphere : film and the feminist imaginary - Lara, María Pía (Northwestern University Press, 2021)
"In Beyond the Public Sphere: Film and the Feminist Imaginary, the renowned philosopher and critical theorist María Pía Lara challenges the notion that the bourgeois public sphere is the most important informal institution between social and political actors and the state. Drawing on a wide range of films--including The Milk of Sorrow, Ixcanul, Wadja, The Stone of Patience, Marnie, A Streetcar Named Desire, and Talk to Her--Lara dissects cinematic images of women's struggles and their oppression. She builds on this analysis, developing a concept of the feminist social imaginary as a broader and more complex space that provides a way of thinking through the possibilities for emancipatory social transformation in response to forms of domination perpetuated by patriarchal capitalism."--Publisher description